Tissue and peripheral eosinophilia as predictors for disease outcome in children with ulcerative colitis. Issue 2 (February 2017) - Morgenstern, Sara; Brook, Elena; Rinawi, Firas; Shamir, Raanan; Assa, Amit
Abstract: Background: Eosinophils are implicated in the pathogenesis of ulcerative colitis. Aims: To evaluate the magnitude of mucosal and blood eosinophils in newly diagnosed pediatric ulcerative colitis patients and its significance in predicting disease outcomes. Methods: We retrospectively evaluated colorectal biopsies of 96 pediatric patients with ulcerative colitis and 50 age- and sex-matched controls. Samples were taken from diseased areas of the colon and examined by a gastrointestinal pathologist. The most inflamed site was used for assessment of mucosal eosinophils. Results: Samples from 96 diagnostic and 70 follow-up colonoscopies were evaluated. Median age was 13.3 years (IQR 10.1–15.3). Median duration of follow-up was 12.8 years (IQR 7.2–17.1). Median number of tissue eosinophils at diagnosis was 45 (IQR 22–73) compared to 10 eosinophils (IQR 8–25) during histologic remission (p < 0.0001). Peripheral absolute eosinophil counts correlated with tissue inflammation and eosinophilia (p = 0.001). Mucosal eosinophilic infiltration (p = 0.02) and peripheral eosinophilia (p = 0.04) was associated with clinical severity at diagnosis. Multivariate analysis showed that severe eosinophilic infiltration is associated with corticosteroid therapy following diagnosis (p = 0.04) but not with long-term risk for step-up therapy or colectomy. Conclusion: Tissue and peripheral eosinophilia correlate with ulcerative colitis severity at diagnosis and with short-term corticosteroid requirement but not with long-term outcomes.